Polymer Film
Patent Information
- Application Number
- JP2021180572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-24
- Filing Date
- 2021-11-04
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-06-29
AI Technical Summary
【0014】 本発明の実現例による高分子フィルムは、優れた静的曲げ特性、光学的物性、および機械的物性を示すのみならず、高温、高湿の過酷な条件下においても優れた光学的物性および機械的物性を保持することができる。
Smart Images

Figure 0007638196000040 
Figure 0007638196000041 
Figure 0007638196000042
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer film that is excellent in static bending properties, folding properties, and transparency, and that retains excellent optical properties and mechanical properties even under high temperature and high humidity conditions. [Background technology]
[0002] Polyimide resins such as poly(amide-imide) (PAI) have excellent resistance to friction, heat, and chemicals, and are used in primary electrical insulation materials, coating agents, adhesives, extrusion resins, heat-resistant paints, heat-resistant boards, heat-resistant adhesives, heat-resistant fibers, and heat-resistant films.
[0003] Polyimides are used in a variety of fields. For example, polyimides are made into powder form and used as coatings for metals or magnet wires, and are mixed with other additives depending on the application. Polyimides are also used as paints for decoration and corrosion prevention together with fluoropolymers, and serve to adhere the fluoropolymers to metal substrates. Polyimides are also used for coating kitchen utensils, and are characterized by their heat and chemical resistance, and are also used as membranes for gas separation, and are used in filtration devices for contaminants such as carbon dioxide, hydrogen sulfide, and impurities in natural gas wells.
[0004] Recently, polyimide-based films have been developed that are less expensive and have excellent optical, mechanical, and thermal properties by forming polyimides into films. Such polyimide-based films can be used as display materials for organic light-emitting diodes (OLEDs) or liquid crystal displays (LCDs), and can be used as anti-reflection films, compensation films, or retardation films to realize retardation properties.
[0005] Such polyimide films have the problem of forming a barrier layer, which exhibits fragile properties that deteriorate in high temperature and high humidity environments. To solve this problem, additives such as clay, which has high moisture resistance, are sometimes introduced, but this can lead to problems such as deterioration of optical properties and poor compatibility.
[0006] In addition, such polyimide films have a problem in that their recovery decreases when they are kept folded for a long time, which can cause screen distortion when used in foldable displays.
[0007] Recently, as development of foldable and flexible displays has been vigorously pursued, there is a continuous demand for research on the development of films that have excellent properties of returning to their original state as much as possible when flattened after being folded for a long time, and that have excellent properties of enduring repeated folding, as well as films that have excellent mechanical and optical properties while maintaining excellent physical properties even in high temperature and high humidity environments. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a polymer film that is excellent in static bending properties, folding properties, and transparency, and that retains excellent optical properties and mechanical properties even under high temperature and high humidity conditions. [Means for solving the problem]
[0009] The polymer film according to one embodiment of the present invention includes a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins, and has a haze (HZ0) of 3% or less before autoclaving, and a ΔHZ represented by the following formula 1a: 24 The value is less than or equal to 500%.
[0010] <Formula 1a> JPEG0007638196000001.jpg1382 In the formula 1a, HZ0 means the haze of the film before autoclaving; HZ 24 is the haze after the film is autoclaved, The autoclave treatment means filling an autoclave with water and then treating at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours.
[0011] According to another embodiment of the present invention, the polymer film includes a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins, and has a modulus (MO0) of 5 GPa or more before autoclaving, and a ΔTS represented by the following formula 1b: 24 The value is 15% or less.
[0012] <Formula 1b> JPEG0007638196000002.jpg1588 In the above formula 1b, TS0 means the tensile strength of the film before autoclaving; TS 24 is the tensile strength after the film is autoclaved, which means that the autoclave is filled with water and then treated at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours.
[0013] A polymer film according to another embodiment of the present invention includes a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins, and butanoic acid. Effect of the Invention
[0014] The polymer film according to the embodiment of the present invention not only exhibits excellent static bending properties, optical properties, and mechanical properties, but also retains excellent optical properties and mechanical properties even under harsh conditions such as high temperature and high humidity.
[0015] In addition, the polymer film according to the embodiment of the present invention has excellent restorability when the force applied to the film is released and the film returns to a flat state after being folded for a long time, so that a uniform screen state can be realized when applied to a foldable display, a flexible display, etc.
[0016] Furthermore, the polymer film according to the embodiment of the present invention can achieve excellent folding properties, and therefore can be usefully applied to cover windows for display devices, as well as foldable display devices, rollable display devices, and flexible display devices. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 shows a cross-sectional view of a display device according to one implementation. [Diagram 2] FIG. 2 is a diagram showing a schematic procedure of a method for producing a polymer film according to one embodiment. [Diagram 3] FIG. 3 is a schematic diagram of a polymer film processing facility according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in order to enable those skilled in the art to easily carry out the present invention. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.
[0019] In this specification, when each film, window, panel, or layer is described as being formed "on" or "under" each film, window, panel, or layer, "on" and "under" include those formed "directly" or "indirectly through other components. In addition, the reference to the top / bottom of each component is described based on the drawings. Note that the size of each component in the drawings may be exaggerated for the purpose of explanation and does not represent the size actually applied. In addition, the same reference symbols refer to the same components throughout the specification.
[0020] In this specification, when a part is said to "comprise" a certain component, this does not mean that it excludes other components, but that it may further include other components, unless specifically stated to the contrary.
[0021] In this specification, the singular expressions are to be construed as including the singular or plural as the context requires, unless otherwise specified.
[0022] Additionally, all numbers and expressions expressing quantities of components, reaction conditions, and the like described herein should be understood to be modified in all instances by the term "about," unless otherwise specified.
[0023] In this specification, the terms "first", "second", etc. are used to describe various components, and the components should not be limited by the terms. The terms are used only to distinguish one component from another.
[0024] In addition, in this specification, unless otherwise specified, the term "substituted" means substituted with one or more substituents selected from the group consisting of deuterium, -F, -Cl, -Br, -I, a hydroxyl group, a cyano group, a nitro group, an amino group, an amidino group, a hydrazine group, a hydrazone group, an ester group, a ketone group, a carboxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted alkynyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted alicyclic organic group, a substituted or unsubstituted heterocyclic group, a substituted or unsubstituted aryl group, and a substituted or unsubstituted heteroaryl group, and the above-mentioned exemplary substituents may be bonded to each other to form a ring.
[0025] <Polymer film> The realization example provides a polymer film that is excellent in static bending properties, folding properties, optical properties, and mechanical properties, and that retains the excellent optical properties and mechanical properties even under high temperature and high humidity conditions.
[0026] The polymeric film according to one implementation includes a polymeric resin selected from the group consisting of polyamide-based resins and polyimide-based resins.
[0027] The haze (HZ0) of the polymer film before autoclave treatment is 3% or less.
[0028] Specifically, the haze (HZ0) of the polymer film before autoclaving may be, but is not limited to, 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, 0.8% or less, or 0.6% or less.
[0029] The polymer film has a ΔHZ represented by the following formula 1a: 24 The value is less than or equal to 500%.
[0030] <Formula 1a> JPEG0007638196000003.jpg1382 In the formula 1a, HZ0 means the haze of the film before autoclaving; HZ 24 is the haze after the film is autoclaved, The autoclave treatment means filling an autoclave with water and then treating for 24 hours at a temperature of 120° C. and a pressure of 1.2 atm. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0031] Specifically, the polymer film has a ΔHz represented by the formula 1a. 24 The value can be, but is not limited to, 400% or less, 300% or less, 250% or less, or 200% or less.
[0032] The haze (HZ0) before autoclaving the polymer film and ΔHZ represented by the above formula 1a 24 When the values are within the above ranges, the film has excellent durability even after being subjected to harsh conditions of high temperature and high humidity, and in particular, a film with little deformation in optical properties can be realized. Due to such characteristics, the film can be easily applied to display front panels and display devices.
[0033] The yellowness index (YI0) of the polymer film before autoclaving is 3 or less.
[0034] Specifically, the yellowness index (YI0) of the polymer film before autoclaving may be 2.8 or less, or 2.7 or less, but is not limited thereto.
[0035] The polymer film has an in-plane retardation (Ro0) of 180 nm or less before autoclaving.
[0036] Specifically, the in-plane retardation (Ro0) of the polymer film before autoclaving can be, but is not limited to, 170 nm or less, 160 nm or less, 150 nm or less, 10 nm to 160 nm, 20 nm to 160 nm, 50 nm to 160 nm, or 80 nm to 150 nm.
[0037] The polymer film has a ΔYI represented by the following formula 2a: 24 The value is 30% or less.
[0038] <Formula 2a> JPEG0007638196000004.jpg1588 In the formula 2a, YI0 means the yellowness of the film before autoclaving; YI 24 is the yellowness of the film after autoclaving, The autoclave treatment means filling an autoclave with water and then treating for 24 hours at a temperature of 120° C. and a pressure of 1.2 atm. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0039] Specifically, the polymer film has a ΔYI represented by the formula 2a. 24 The value can be, but is not limited to, 25% or less, 20% or less, 15% or less, 10% or less, or 5% or less.
[0040] The polymer film has a ΔRo represented by the following formula 3a: 24 The value is 8% or less.
[0041] <Formula 3a> JPEG0007638196000005.jpg1588 In the formula 3a, Ro0 means the in-plane retardation before the film is autoclaved, Ro 24is the in-plane retardation after the film is autoclaved, The autoclave treatment means filling an autoclave with water and then treating for 24 hours at a temperature of 120° C. and a pressure of 1.2 atm. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0042] Specifically, the polymer film has a ΔRo represented by the formula 3a. 24 The value can be, but is not limited to, 7% or less, 6% or less, 5% or less, or 4.8% or less.
[0043] The haze (HZ) of the polymer film after 24 hours of autoclave treatment 24 ) is 3% or less. The autoclave treatment means filling an autoclave with water and then treating at a temperature of 120°C and a pressure of 1.2 atm for 24 hours. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0044] Specifically, the haze (HZ) of the polymer film after 24 hours of autoclave treatment was 24 ) may be, but is not limited to, 2.5% or less, 2.0% or less, 1.8% or less, or 1.6% or less.
[0045] The yellowness index (YI) of the polymer film after 24 hours of autoclave treatment 24 ) is 3 or less. The autoclave treatment means filling an autoclave with water and then treating at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0046] Specifically, the yellowness index (YI) of the polymer film after 24 hours of autoclave treatment was 24) may be, but is not limited to, 2.8 or less, or 2.7 or less.
[0047] In particular, the yellowness index (YI) of the polymer film after 24 hours of autoclave treatment was 24 ) exceeds the above range, transparency decreases in a hot and humid environment, making it unsuitable for use as a front panel or display device to which the film is applied. Furthermore, the screen appears blurred and dark, and in order to compensate for this, more power is consumed to maintain a brighter screen state.
[0048] The in-plane retardation (Ro) of the polymer film after 24 hours of autoclave treatment 24 ) is 180 nm or less. The autoclave treatment means filling an autoclave with water and then treating at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours. After being placed in the autoclave, the film is not immersed in the water and can be treated by the water vapor generated by the water.
[0049] Specifically, the in-plane retardation (Ro 24 ) can be, but is not limited to, 160 nm or less, 150 nm or less, 145 nm or less, 20 nm to 160 nm, 40 nm to 150 nm, or 60 nm to 145 nm.
[0050] In particular, the polymer film of the embodiment has a low ΔHZ 24 Value, ΔYI 24 value, and ΔRo 24 Since the polymer film has excellent optical properties even under harsh conditions such as high temperature and humidity, it can be easily applied to a display device, and even when a display device using the polymer film is used in a humid or hot area, it can still provide a clear and clear screen.
[0051] Furthermore, the polymer film according to the embodiment has HZ0, YI0, Ro0, and HZ0 in the above-mentioned ranges.24 , Y.I. 24 , Ro 24 , ΔHZ 24 Value, ΔYI 24 value, and ΔRo 24 By having such a value, not only clear optical characteristics but also excellent folding characteristics can be realized, and therefore it is suitable for application to a foldable display device or a flexible display device.
[0052] The tensile strength (TS0) of the polymer film before autoclave treatment is 20Kgf / mm 2 That's all.
[0053] Specifically, the tensile strength (TS0) of the polymer film before autoclave treatment is 20 kgf / mm 2 ~35Kgf / mm 2 Or, the tensile strength (TS0) of the polymer film before autoclave treatment is 21 kgf / mm 2 It may be more than this, but is not limited to this.
[0054] The polymer film has a breaking elongation (EL0) of 15% or more before autoclave treatment.
[0055] Specifically, the elongation at break (EL0) of the polymer film before autoclaving is 15% to 40%, or may be 17% or more, 18% or more, 19% or more, or 20% or more, but is not limited thereto.
[0056] The modulus (MO0) of the polymer film before autoclave treatment is 5 GPa or more.
[0057] Specifically, the modulus (MO0) of the polymer film before autoclaving is 5 GPa to 10 GPa, or may be 5.2 GPa or more, 5.3 GPa or more, or 5.5 GPa or more, but is not limited thereto.
[0058] The polymer film has a ΔTS represented by the following formula 1b: 24 The value is less than 15%.
[0059] <Formula 1b> In the formula 1b, TS0 means the tensile strength of the film before autoclaving, and TS 24 is the tensile strength after the film is treated in an autoclave, and the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours. After being placed in the autoclave, the film is not immersed in the water, but can be treated by the water vapor generated by the water.
[0060] Specifically, the TS 24 is 20Kgf / mm 2 That's all.
[0061] In addition, the ΔTS of the polymer film 24 The value can be, but is not limited to, 12% or less, 10% or less, or 8.5% or less.
[0062] The polymer film has a ΔEL represented by the following formula 2b: 24 The value is below 30%.
[0063] <Formula 2b> In the formula 2b, EL0 means the breaking elongation of the film before the autoclave treatment, and EL 24is the breaking elongation after the film is treated in an autoclave, and the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours. After being placed in the autoclave, the film is not immersed in the water, but can be treated by the water vapor generated by the water.
[0064] Specifically, the EL 24 is 15% or more. 24 can be, but is not limited to, 17% or more or 20% or more.
[0065] In addition, the ΔEL of the polymer film 24 The value can be, but is not limited to, 28% or less or 25% or less.
[0066] The polymer film has a ΔMO represented by the following formula 3b: 24 The value is less than 15%.
[0067] <Formula 3b> In the formula 3b, MO0 means the modulus of the film before autoclaving, and MO 24 is the modulus after the film is treated in an autoclave, where the autoclave treatment means filling the autoclave with water and treating for 24 hours at a temperature of 120° C. and a pressure of 1.2 atm. After the film is placed in the autoclave, it is not immersed in the water, but can be treated by the water vapor generated by the water.
[0068] Specifically, the MO 24 is 15% or more. 24 can be, but is not limited to, 5 GPa or more, 5.1 GPa or more, 5.5 GPa or more, or 6.0 GPa or more.
[0069] In addition, the ΔMO of the polymer film24 The value can be, but is not limited to, 12% or less or 10% or less.
[0070] ΔSUM of the polymer film 24 The value is 60% or less. 24 The value is the ΔTS 24 , ΔEL 24 and ΔMO 24 This is a value that indicates the sum of.
[0071] Specifically, the ΔSUM of the polymer film 24 The value can be, but is not limited to, 50% or less, 40% or less, or 35% or less.
[0072] ΔTS of the polymer film 24 , ΔEL 24 , ΔMO 24 and ΔSUM 24 By satisfying the above range, the film has excellent durability even under high temperature and high humidity conditions, and the physical properties are hardly changed, so that the film can be easily applied to front panels and display devices.
[0073] The polymer film has a ΔTS represented by the following formula 4b: 72 The value is below 60%.
[0074] <Formula 4b> In the formula 4b, TS0 means the tensile strength before the film is autoclaved, and TS 72 is the tensile strength after the film is treated in an autoclave, and the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 72 hours. After being placed in the autoclave, the film is not immersed in the water, but can be treated by the water vapor generated by the water.
[0075] Specifically, the TS 72 is 5Kgf / mm2 Over 8Kgf / mm 2 or more than 9Kgf / mm 2 That's all.
[0076] In addition, the ΔTS of the polymer film 72 The value can be, but is not limited to, 50% or less, 40% or less, or 30% or less.
[0077] The polymer film has a ΔEL represented by the following formula 5b: 72 The value is less than 50%.
[0078] <Formula 5b> In the formula 5b, EL0 means the breaking elongation before the film is treated in an autoclave, and EL 72 is the breaking elongation after the film is treated in an autoclave, and the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 72 hours. After being placed in the autoclave, the film is not immersed in the water, but can be treated by the water vapor generated by the water.
[0079] Specifically, the EL 72 is 8% or more, 10% or more, or 12% or more.
[0080] In addition, the ΔEL of the polymer film 72 The value can be, but is not limited to, 45% or less or 40% or less.
[0081] The polymer film has a ΔMO represented by the following formula 6b: 72 The value is 60% or less.
[0082] <Formula 6b> In the formula 6b, MO0 means the modulus of the film before autoclaving, and MO 72 is the modulus after the film is treated in an autoclave, where the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 72 hours. After the film is placed in the autoclave, it is not immersed in the water, but can be treated by the water vapor generated by the water.
[0083] Specifically, the MO 72 is 2 GPa or more or 2.5 GPa or more.
[0084] In addition, the ΔMO of the polymer film 72 The value can be, but is not limited to, 50% or less, 40% or less, 30% or less, or 20% or less.
[0085] ΔSUM of the polymer film 72 The value is 160% or less. 72 The value is the ΔTS 72 , ΔEL 72 and ΔMO 72 This is a value that indicates the sum of.
[0086] Specifically, the ΔSUM of the polymer film 72 The value can be, but is not limited to, 150% or less, 120% or less, 100% or less, or 90% or less.
[0087] ΔTS of the polymer film 72 , ΔEL 72 , ΔMO 72 and ΔSUM 72 By satisfying the above range, the film has excellent durability even under high temperature and high humidity conditions and is hardly deformed in physical properties, so that it can be easily applied to front panels and display devices.
[0088] When the polymer film according to the embodiment is folded to a curvature radius of 3 mm based on a thickness of 50 μm, it can be folded more than 100,000 times before breaking.
[0089] The number of times of folding is defined as one time of folding and unfolding the film so that the radius of curvature of the film is 3 mm.
[0090] Since the polymer film satisfies the folding number within the above range, it can be usefully applied to a foldable display device or a flexible display device.
[0091] Another embodiment of the polymer film can be folded more than 200,000 times before breaking when folded to a radius of curvature of 2 mm based on a thickness of 50 μm.
[0092] The number of times of folding is defined as one time of folding and unfolding the film so that the radius of curvature of the film is 2 mm.
[0093] The residual solvent content in the polymer film according to the embodiment is 2500 ppm or less, or 1200 ppm or less.
[0094] For example, the content of the residual solvent may be, but is not limited to, 2200 ppm or less, 2000 ppm or less, 1800 ppm or less, 1500 ppm or less, 1000 ppm or less, 800 ppm or less, 500 ppm or less, 1 ppm to 1000 ppm, 1 ppm to 800 ppm, 1 ppm to 500 ppm, 5 ppm to 1000 ppm, 10 ppm to 1000 ppm, or 20 ppm to 1000 ppm.
[0095] The residual solvent refers to the amount of solvent that is not volatilized during the film production and remains in the final film.
[0096] If the content of the residual solvent in the polymer film exceeds the above range, the durability and optical properties of the film may be reduced under high temperature and high humidity conditions, and may affect the post-processing of the film. Specifically, if the content of the residual solvent exceeds the above range, the hydrolysis of the film may be accelerated, and the mechanical properties or optical properties may be reduced. In addition, if the content of the residual solvent in the polymer film exceeds the above range, the durability of the film may be reduced, and the bending resistance properties such as the static bending properties and folding properties may also be affected.
[0097] According to the embodiment, the IS value of the polymer film is 5 to 160, as expressed by the following formula 7.
[0098] <Formula 7> JPEG0007638196000012.jpg1133In the above formula 7, IM means the number of moles of imide repeating units when the total number of moles of imide repeating units and amide repeating units in the film is 100, and RS means the content (ppm) of residual solvent in the film.
[0099] For example, the IS value may be 5 to 150, or 10 to 150, 30 to 150, or 50 to 150, 5 to 80, 5 to 60, or 5 to 50, but is not limited thereto.
[0100] When the IS value of the polymer film satisfies the above range, a film having excellent optical properties, durability, and folding properties can be realized even after treatment under harsh conditions of high temperature and high humidity.
[0101] In particular, if the imide content (IM) is high or the residual solvent content (RS) in the film is high and exceeds the above range, the long-term durability of the film drops sharply. Specifically, if the imide content is too high and the amide content is relatively low, the film's moisture absorption drops, and the film may exhibit weak properties under high humidity conditions.
[0102] The polymer film has a CT value represented by the following formula 8 of 10 or less.
[0103] <Formula 8> In the above formula 8, HZ0 means the haze before the film is treated in an autoclave, and HZ 24 is the haze after the film is treated in an autoclave, where the autoclave treatment means filling the autoclave with water and treating it at a temperature of 120° C. and a pressure of 1.2 atm for 24 hours. After the film is placed in the autoclave, it is not immersed in the water, but can be treated by the water vapor generated by the water.
[0104] Moreover, Ro0 means the in-plane retardation before the film is treated in an autoclave.
[0105] The CT can be an index representing heat resistance / humidity resistance reflecting crystallinity. The higher the crystallinity of the polymer film, the lower the ΔHZ 24 In other words, the higher the crystallinity of the polymer film, the higher the heat resistance / humidity resistance of the polymer film. The higher the crystallinity of the polymer film, the higher the in-plane retardation (Ro0) and the lower the optical properties of the polymer film.
[0106] The polymer film may have an improved heat / humidity resistance while having the improved optical properties by being manufactured with a suitable composition and a suitable process. For example, the polymer film may have a relatively high amide content, a low residual solvent content, an additive such as butyric acid, and a suitable process such as a drying process and a heat treatment process. As a result, the polymer film may have a low in-plane retardation and a high ΔHZ 24 can be lowered at the same time.
[0107] Thus, the CT may be 10 or less. The CT may be 8 or less. The CT may be 6 or less. The CT may be 4 or less. The CT may be 4 or less. The CT may be 3 or less. The CT may be 2 or less.
[0108] The polymer film has a low CT, and therefore has improved heat / humidity resistance and improved optical properties. As a result, the polymer film can be effectively used for displays. Specifically, the polymer film can be effectively applied to mobile display devices that are easily exposed to harsh external conditions such as moisture and / or heat. In particular, the polymer film can be effectively applied to the front panel of a foldable display.
[0109] The polymer film according to the embodiment may further include butyric acid in addition to the polymer resin.
[0110] According to an embodiment, the polymer film includes a polymer resin and butyric acid. The polymer resin includes a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins. The polymer film includes a polymer resin, and the polymer resin includes a plurality of imide repeat units. The butyric acid is represented by the following chemical formula T.
[0111] <KaT> JPEG0007638196000014.jpg2143
[0112] Specifically, the butyric acid refers to a compound represented by the chemical formula T, and does not refer to a partially substituted form of the butyric acid, a derivative, a salt, an anhydride, etc. of the butyric acid.
[0113] The polymer film contains butyric acid, and the butyric acid is contained in the film in an amount of 1 ppm to 1200 ppm based on the total weight of the polymer film.
[0114] Specifically, the butyric acid may be contained in the film at a concentration of 1 ppm to 1000 ppm, 5 ppm to 1000 ppm, 10 ppm to 1000 ppm, 50 ppm to 1000 ppm, 100 ppm to 1000 ppm, 500 ppm to 1000 ppm, 1 ppm to 800 ppm, 1 ppm to 700 ppm, 1 ppm to 500 ppm, 1 ppm to 300 ppm, 10 ppm to 300 ppm, 30 ppm to 300 ppm, or 50 ppm to 270 ppm, but is not limited thereto.
[0115] The content means the content of butyric acid that is not volatilized during the film production and remains in the final film produced.
[0116] If the content of butyric acid in the polymer film exceeds the above range, some substances may be eluted onto the film after autoclaving, causing a problem of a rapid increase in the haze of the film.
[0117] The butyric acid may be, but is not limited to, but may be a by-product generated during other reactions or may be butyric acid added as a pH adjuster during the film manufacturing process, i.e., butyric acid remaining in the final film may be generated through various processes.
[0118] Due to the presence of butyric acid remaining in the polymer film, the film has excellent restorability and folding characteristics when it is restored to a flat state by releasing the force applied to the film after being folded for a long time, and is therefore easily applicable to foldable displays, flexible displays, rollable displays, and the like.
[0119] If the content of butyric acid remaining in the polymer film exceeds the above range, the static bending property and folding property of the film may be deteriorated, and optical properties such as transmittance and yellowness index may also be deteriorated.
[0120] In one embodiment, a polymer film having a thickness of 50 μm is folded to have a radius of curvature of 2 mm and left at 25° C. for 24 hours, and then when the force applied to the film is released, the internal angle of the film is 120° or more.
[0121] Specifically, when the polymer film is folded to have a radius of curvature of 2 mm based on a thickness of 50 μm, left at 25° C. for 24 hours, and then the force applied to the film is released, the internal angle of the film may be, but is not limited to, 125° or more, 130° or more, or 135° or more.
[0122] Conventional films are vulnerable to external pressure, and especially after being folded for a long period of time, they are subject to significant deformation, and when applied to display devices, they are unable to show a uniform screen state, causing problems such as screen distortion. Specifically, when a conventional film is folded to a thickness of 50μm with a radius of curvature of 2mm and left at 25°C for 24 hours, and then the force applied to the film is released, the internal angle of the film is less than 120°, specifically 115° or less, resulting in poor static bending resistance.
[0123] Meanwhile, the polymer film of the realization example achieved an internal angle of 120° or more in the above experiment, ensuring better restoring force than conventional films. When a film with such characteristics is applied to post-processing (for example, when applied to foldable displays or flexible displays), it solves problems such as screen distortion.
[0124] In another embodiment, the polymer film has a stretch ratio in the MD (Machine Direction) of 1.01 to 1.15.
[0125] By making the stretch ratio in the MD direction of the polymer film according to the embodiment satisfy the above range, when the force applied to the film is released and the film is restored to a flat state after being folded for a long time, the film undergoes little deformation, has excellent folding characteristics, and is highly durable against physical impact. Specifically, the stretching causes crystallization due to orientation within the film, which results in a film with excellent bending resistance.
[0126] If the stretch ratio in the MD direction of the polymer film according to the embodiment is outside the above range, the restoration properties of the film are particularly deteriorated, making it difficult to achieve the desired physical properties.
[0127] The polyamide resin is a resin containing an amide repeating unit, and the polyimide resin is a resin containing an imide repeating unit.
[0128] In addition, a resin containing the imide repeating unit and the amide repeating unit can be called the polyamide-based resin or the polyimide-based resin.
[0129] For example, the polymer resin may be a resin containing a polyamide-based resin, a resin containing a polyimide-based resin, or a resin containing both a polyamide-based resin and a polyimide-based resin.
[0130] The polymeric film according to one implementation includes a polymeric resin formed by polymerizing a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound.
[0131] In one embodiment, the molar ratio of the dianhydride compound to the dicarbonyl compound is 2:98 to 50:50, 5:95 to 50:50, 10:90 to 50:50, 2:98 to 25:75, 2:98 to 15:85, 20:80 to 100:0, 25:75 to 100:0, 30:70 to 100:0, 40:60 to 100:0, or 50:50 to 100:0.
[0132] When the molar ratio of the dianhydride compound to the dicarbonyl compound is within the above range, a film having excellent optical properties and strong durability under high temperature and high humidity conditions can be realized. In addition, a film having excellent restoring force when the film is released from a force applied thereto and restored to a flat state after being folded for a long time, and having excellent folding properties and transparency can be realized.
[0133] In another embodiment, the dianhydride compound may be one or more kinds, and the dicarbonyl compound may be zero, one, or two or more kinds.
[0134] The polymer resin contains imide repeating units derived from the polymerization of a diamine compound and a dianhydride compound, and amide repeating units derived from the polymerization of the diamine compound and a dicarbonyl compound.
[0135] The polymer resin may contain imide-based repeating units and amide-based repeating units in a molar ratio of, but is not limited to, 2:98 to 50:50, 5:95 to 50:50, 10:90 to 50:50, 2:98 to 25:75, 2:98 to 15:85, 20:80 to 100:0, 25:75 to 100:0, 30:70 to 100:0, 40:60 to 100:0, or 50:50 to 100:0.
[0136] The diamine compound is a compound that forms a copolymer by forming an imide bond with the dianhydride compound and an amide bond with the dicarbonyl compound.
[0137] The diamine compound is not particularly limited, and may be, for example, an aromatic diamine compound having an aromatic structure. For example, the diamine compound may be a compound represented by the following Formula 1:
[0138] <C1> JPEG0007638196000015.jpg649In the above Chemical Formula 1, E is a substituted or unsubstituted divalent C6-C 30Alicyclic radicals, substituted or unsubstituted divalent C4-C 30 Heteroalicyclic groups, substituted or unsubstituted divalent C6-C 30 Aromatic ring groups, substituted or unsubstituted divalent C4-C 30 Aromatic heterocyclic groups, substituted or unsubstituted C1-C 30 Alkylene groups, substituted or unsubstituted C2-C 30 Alkenylene groups, substituted or unsubstituted C2-C 30 Alkynylene groups may be selected from among -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2, -Si(CH3)2-, -C(CH3)2-, and -C(CF3)2-.
[0139] e is selected from integers of 1 to 5, and when e is 2 or greater, E may be the same or different.
[0140] (E) of Chemical Formula 1 e can be selected from groups represented by the following chemical formulas 1-1a to 1-14a, but is not limited thereto. JPEG0007638196000016.jpg100145
[0141] Specifically, (E) of the above Chemical Formula 1 e can be selected from groups represented by the following chemical formulas 1-1b to 1-13b, but is not limited thereto. JPEG0007638196000017.jpg98145
[0142] More specifically, (E) of the above Chemical Formula 1 e may be a group represented by the above formula 1-6b or a group represented by the above formula 1-9b.
[0143] In one implementation, the diamine compound may include a compound having a fluorine-containing substituent or a compound having an ether group (-O-).
[0144] The diamine compound may be a compound having a fluorine-containing substituent, and the fluorine-containing substituent may be a fluorohydrocarbon group, specifically, a trifluoromethyl group, but is not limited thereto.
[0145] In another embodiment, the diamine compound may be one type of diamine compound, i.e., the diamine compound may consist of a single component.
[0146] For example, the diamine compound may include, but is not limited to, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFDB) having the following structure: JPEG0007638196000018.jpg4476
[0147] Alternatively, the diamine compound may include, but is not limited to, the TFMB and 4,4'-oxydianiline (ODA).
[0148] The dianhydride compound has a low birefringence value, and therefore can contribute to improving optical properties such as transmittance of a film containing the polymer resin. The polymer resin means a polymer containing an imide repeat unit.
[0149] The dianhydride compound is not particularly limited, and may be, for example, an aromatic dianhydride compound containing an aromatic structure or an alicyclic dianhydride compound containing an alicyclic structure. For example, the aromatic dianhydride compound may be a compound represented by the following Formula 2:
[0150] <2> JPEG0007638196000019.jpg3959In the above formula 2, G is a substituted or unsubstituted tetravalent C6-C 30 Alicyclic radicals, substituted or unsubstituted tetravalent C4-C30 Heteroalicyclic groups, substituted or unsubstituted tetravalent C6-C 30 Aromatic ring groups, substituted or unsubstituted, tetravalent C4-C 30 an aromatic heterocyclic group, wherein the alicyclic group, the heteroalicyclic group, the aromatic ring group, or the aromatic heterocyclic group is present alone or joined to each other to form a fused ring, or is a substituted or unsubstituted C-C 30 Alkylene groups, substituted or unsubstituted C2-C 30 Alkenylene groups, substituted or unsubstituted C2-C 30 The alkynylene groups are linked by a linking group selected from among -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2, -Si(CH3)2-, -C(CH3)2-, and -C(CF3)2.
[0151] G in the above formula 2 may be selected from groups represented by the following formulas 2-1a to 2-9a, but is not limited thereto. JPEG0007638196000020.jpg86145
[0152] For example, G in the above formula 2 can be a group represented by the above formula 2-2a, a group represented by the above formula 2-8a, or a group represented by the above formula 2-9a.
[0153] In addition, the alicyclic dianhydride compound may include a cyclobutane structure. Specifically, the alicyclic dianhydride compound may be, but is not limited to, CBDA (cyclobutane-1,2,3,4-tetracarboxylic dianhydride).
[0154] In other implementations, the dianhydride compound can include a compound having a fluorine-containing substituent, a compound having a biphenyl group, a compound having a ketone group, or a compound having a cyclobutane group.
[0155] The dianhydride compound may be a compound having a fluorine-containing substituent, which may be a fluorinated hydrocarbon group, specifically, a trifluoromethyl group, but is not limited thereto.
[0156] In other implementations, the dianhydride compound may consist of one single component or a mixture of two or more components.
[0157] For example, the dianhydride compound may include, but is not limited to, 2,2'-bis-(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) having the following structure: JPEG0007638196000021.jpg3669
[0158] The diamine compound and the dianhydride compound may be polymerized to produce a polyamic acid.
[0159] The polyamic acid can then be converted to a polyimide by a dehydration reaction, the polyimide comprising imide repeat units. The polyimide may form a repeating unit represented by the following chemical formula A:
[0160] <Case A> JPEG0007638196000022.jpg4177 In the above chemical formula A, E, G, and e are as defined above.
[0161] For example, the polyimide may include a repeating unit represented by the following formula A-1, but is not limited thereto.
[0162] <Chemical A-1> JPEG0007638196000023.jpg41131 In the above chemical formula A-1, n is an integer of 1 to 400.
[0163] The dicarbonyl compound is not particularly limited, and may be, for example, a compound represented by the following formula 3:
[0164] <3> In the above formula 3, J is a substituted or unsubstituted divalent C6-C 30 Alicyclic radicals, substituted or unsubstituted divalent C4-C 30 Heteroalicyclic groups, substituted or unsubstituted divalent C6-C 30 Aromatic ring groups, substituted or unsubstituted divalent C4-C 30 Aromatic heterocyclic groups, substituted or unsubstituted C1-C 30 Alkylene groups, substituted or unsubstituted C2-C 30 Alkenylene groups, substituted or unsubstituted C2-C 30 Alkynylene groups may be selected from among -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2, -Si(CH3)2-, -C(CH3)2-, and -C(CF3)2-.
[0165] j is selected from integers of 1 to 5, and when j is 2 or more, J may be the same or different.
[0166] X is a halogen atom. Specifically, X can be F, Cl, Br, I, etc. More specifically, X can be Cl, but is not limited thereto.
[0167] (J) of the above Chemical Formula 3 j can be selected from the groups represented by the following chemical formulas 3-1a to 3-14a, but is not limited thereto. JPEG0007638196000025.jpg95146
[0168] Specifically, (J) of the above Chemical Formula 3 jcan be selected from groups represented by the following chemical formulas 3-1b to 3-8b, but is not limited thereto. JPEG0007638196000026.jpg73148
[0169] More specifically, (J) of the above Chemical Formula 3 j may be a group represented by the chemical formula 3-1b, a group represented by the chemical formula 3-2b, a group represented by the chemical formula 3-3b, or a group represented by the chemical formula 3-8b.
[0170] In one embodiment, the dicarbonyl compound may be one or a mixture of at least two different dicarbonyl compounds. When two or more dicarbonyl compounds are used, the dicarbonyl compound is (J) in Formula 3. j However, two or more types selected from the groups represented by the chemical formulas 3-1b to 3-8b may be used.
[0171] In another implementation, the dicarbonyl compound can be an aromatic dicarbonyl compound that includes an aromatic structure.
[0172] For example, the dicarbonyl compound can include a first dicarbonyl compound and / or a second dicarbonyl compound.
[0173] The first dicarbonyl compound and the second dicarbonyl compound can each be an aromatic dicarbonyl compound.
[0174] The first dicarbonyl compound and the second dicarbonyl compound may be different compounds.
[0175] For example, the first dicarbonyl compound and the second dicarbonyl compound may be different aromatic dicarbonyl compounds, but are not limited thereto.
[0176] When the first dicarbonyl compound and the second dicarbonyl compound are each an aromatic dicarbonyl compound, they contain a benzene ring, which can contribute to improving the mechanical properties, such as the surface hardness and tensile strength, of a film containing the prepared polyamide-imide resin.
[0177] The dicarbonyl compound may include, but is not limited to, terephthaloyl chloride (TPC), 1,1'-biphenyl-4,4'-dicarbonyl dichloride (BPDC), isophthaloyl chloride (IPC), or a combination thereof, having the following structure: JPEG0007638196000027.jpg10372
[0178] For example, the first dicarbonyl compound may include BPDC and the second dicarbonyl compound may include TPC, but is not limited thereto.
[0179] By using an appropriate combination of BPDC as the first dicarbonyl compound and TPC as the second dicarbonyl compound, a film containing the prepared polyamide-imide resin can have high oxidation resistance.
[0180] Alternatively, the first dicarbonyl compound may include IPC and the second dicarbonyl compound may include TPC, but is not limited thereto.
[0181] By using an appropriate combination of IPC as the first dicarbonyl compound and TPC as the second dicarbonyl compound, a film containing the prepared polyamide-imide resin can not only have high oxidation resistance but also be economical because it can reduce costs.
[0182] The diamine compound and the dicarbonyl compound may be polymerized to form a repeating unit represented by the following chemical formula B.
[0183] <Case B> In the above chemical formula B, the explanations for E, J, e, and j are as described above.
[0184] For example, the diamine compound and the dicarbonyl compound can be polymerized to form amide repeat units represented by formulas B-1 and B-2.
[0185] Alternatively, the diamine compound and the dicarbonyl compound may be polymerized to form amide repeat units represented by formulas B-2 and B-3.
[0186] <Case B-1> JPEG0007638196000029.jpg31102 In the chemical formula B-1, x is an integer of 1 to 400.
[0187] <Case B-2> JPEG0007638196000030.jpg3798 In the chemical formula B-2, y is an integer of 1 to 400.
[0188] <Case B-3> JPEG0007638196000031.jpg42104 In the above chemical formula B-3, y is an integer of 1 to 400.
[0189] According to one embodiment, the polymer resin may include a repeating unit represented by the following formula A and, optionally, a repeating unit represented by the following formula B:
[0190] <Case A> JPEG0007638196000032.jpg4786
[0191] <Case B> JPEG0007638196000033.jpg3986 Among the chemical formulas A and B, E and J are each independently a substituted or unsubstituted divalent C6-C 30 Alicyclic radicals, substituted or unsubstituted divalent C4-C 30 Heteroalicyclic groups, substituted or unsubstituted divalent C6-C 30 Aromatic ring groups, substituted or unsubstituted divalent C4-C 30 Aromatic heterocyclic groups, substituted or unsubstituted C1-C 30 Alkylene groups, substituted or unsubstituted C2-C 30 Alkenylene groups, substituted or unsubstituted C2-C 30 alkynylene groups selected from -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2, -Si(CH3)2-, -C(CH3)2, and -C(CF3)2; e and j are each independently selected from integers of 1 to 5; When e is 2 or more, the 2 or more E's may be the same or different. When j is 2 or more, two or more Js may be the same or different. G is a substituted or unsubstituted tetravalent C6-C 30 Alicyclic radicals, substituted or unsubstituted tetravalent C4-C 30 Heteroalicyclic groups, substituted or unsubstituted tetravalent C6-C 30 Aromatic ring groups, substituted or unsubstituted, tetravalent C4-C 30 an aromatic heterocyclic group, wherein the alicyclic group, the heteroalicyclic group, the aromatic ring group, or the aromatic heterocyclic group is present alone or joined to each other to form a fused ring, or is a substituted or unsubstituted C-C 30 Alkylene groups, substituted or unsubstituted C2-C 30 Alkenylene groups, substituted or unsubstituted C2-C 30 The alkynylene groups are linked by a linking group selected from among -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2, -Si(CH3)2-, -C(CH3)2-, and -C(CF3)2.
[0192] In the polymer resin, the molar ratio of the repeating unit represented by the chemical formula A to the repeating unit represented by the chemical formula B may be, but is not limited to, 2:98 to 50:50, 5:95 to 50:50, 10:90 to 50:50, 2:98 to 25:75, 2:98 to 15:85, 20:80 to 100:0, 25:75 to 100:0, 30:70 to 100:0, 40:60 to 100:0, or 50:50 to 100:0.
[0193] When the molar ratio of the repeating unit represented by the chemical formula A and the repeating unit represented by the chemical formula B is within the above range, the polymer film has excellent folding properties and excellent optical and mechanical properties under high temperature and high humidity conditions.
[0194] Specifically, the CONH structure present in the repeating unit represented by chemical formula B has high affinity with OH groups and exhibits excellent moisture absorption properties that attract moisture, thereby imparting slip properties to the film, making it possible to realize a film that exhibits almost no deterioration in mechanical strength and optical properties even under high temperature and high humidity conditions.
[0195] According to another embodiment, the polymer film may further include a filler.
[0196] The filler may be one or more selected from the group consisting of barium sulfate, silica, and calcium carbonate. By including the filler, the polymer film can improve the illuminance and winding property, as well as the running property during film production and the scratch prevention effect.
[0197] The particle size of the filler may be 0.01 μm to 1.0 μm, or 0.01 μm or more to less than 1.0 μm. For example, the particle size of the filler may be, but is not limited to, 0.05 μm to 0.9 μm, 0.1 μm to 0.8 μm, 0.1 μm to 0.5 μm, or 0.1 μm to 0.3 μm.
[0198] The polymer film may contain the filler in an amount of 0.01 wt % to 3.5 wt %, 0.01 wt % to 3 wt %, or 0.01 wt % to 2.5 wt %, based on the total weight of the polymer film.
[0199] The polymer film may have a transmittance of 80% or more. For example, the transmittance may be 85% or more, 88% or more, 89% or more, 80% to 99%, 85% to 99%, or 88% to 99%.
[0200] The polymer film has a yellow index of 5 or less. For example, the yellow index may be 4 or less or 3.5 or less, but is not limited thereto.
[0201] The haze of the polymer film is 2% or less. Specifically, the haze may be, but is not limited to, 1.8% or less, 1.5% or less, 1% or less, 0.8% or less, or 0.5% or less.
[0202] The modulus of the polymer film is 4.0 GPa or more, 4.2 GPa or more, 4.5 GPa or more, or 5.0 GPa or more. Specifically, the modulus may be 5.5 GPa or more, 6.0 GPa or more, 6.2 GPa or more, or 6.0 GPa to 8.0 GPa, but is not limited thereto.
[0203] The polymer film has a compressive strength of 0.3 kgf / μm or more. Specifically, the compressive strength may be, but is not limited to, 0.4 kgf / μm or more, 0.45 kgf / μm or more, or 0.48 kgf / μm or more.
[0204] When the polymer film is perforated in UTM compression mode using a 2.5 mm spherical tip at a speed of 10 mm / min, the maximum diameter of the perforation including cracks (mm) is 65 mm or less. Specifically, the maximum diameter of the perforation may be, but is not limited to, 60 mm or less, 5 mm to 60 mm, 10 mm to 60 mm, 15 mm to 60 mm, 20 mm to 60 mm, 25 mm to 60 mm, or 25 mm to 58 mm.
[0205] The polymer film has a surface hardness of HB or more. Specifically, the surface hardness may be H or more or 2H or more, but is not limited thereto.
[0206] The polymer film has a tensile strength of 14 kgf / mm 2 Specifically, the tensile strength is 15 kgf / mm 2 More than 16kgf / mm 2 Above, 18kgf / mm 2 Above 20kgf / mm 2 Above, 21kgf / mm 2 or more than 22kgf / mm 2 It may be more than this, but is not limited to this.
[0207] The polymer film has an elongation percentage of 13% or more. Specifically, the elongation percentage may be, but is not limited to, 15% or more, 16% or more, 17% or more, or 17.5% or more.
[0208] The polymer film according to one embodiment has excellent optical properties such as low haze and low yellowness index (YI), and excellent mechanical properties such as high modulus, compressive strength, maximum perforation diameter, surface hardness, tensile strength, and elongation, as well as excellent folding properties and excellent optical and mechanical properties even under high temperature and humidity. As a result, it is possible to realize long-term stable mechanical and optical properties for substrates that require flexibility in terms of modulus, elongation, tensile properties, elastic recovery force, and bending resistance.
[0209] The above-mentioned physical properties of the polymer film are based on a thickness of 40 μm to 60 μm or a thickness of 70 μm to 90 μm, for example, based on a thickness of 50 μm or a thickness of 80 μm.
[0210] The features regarding the components and physical properties of the polymer film described above can be combined with each other.
[0211] The above-mentioned physical properties of the polymer film are the result of a combination of the chemical and physical properties of the components constituting the polymer film as well as the process conditions of each step in the method of manufacturing the polymer film, which will be described later.
[0212] [Display front panel] A front plate for a display according to one implementation includes a polymeric film and a functional layer.
[0213] The polymer film includes a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins.
[0214] According to one embodiment, the polymer film has a haze (HZ0) of 3% or less before autoclaving, and a ΔHZ value expressed by the above formula 1a. 24 The value is less than or equal to 500%.
[0215] According to another embodiment, the polymer film has a modulus (MO) before autoclaving of 5 GPa or more, and a ΔTS represented by the above formula 1b. 24 The value is 15% or less.
[0216] Yet another implementation of the polymeric film includes a polymeric resin and butyric acid. The polymer film has been specifically described above.
[0217] The front plate may be usefully applied to a display device.
[0218] The polymer film has excellent folding properties and can maintain excellent optical and mechanical properties even under harsh conditions such as high temperature and high humidity. In particular, since not only the polymer film but also the functional layer has excellent folding properties, the front panel can be usefully applied to a foldable display device or a flexible display device.
[0219] [Display device] A display device according to one implementation includes a display portion and a front panel disposed on the display portion, the front panel including a polymer film.
[0220] The polymer film may include a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins.
[0221] According to one embodiment, the polymer film has a haze (HZ0) of 3% or less before autoclaving, and a ΔHZ value expressed by the above formula 1a. 24 The value is less than or equal to 500%.
[0222] According to another embodiment, the polymer film has a modulus (MO) before autoclaving of 5 GPa or more, and a ΔTS represented by the above formula 1b. 24 The value is 15% or less.
[0223] Yet another implementation of the polymeric film includes a polymeric resin and butyric acid. The polymer film and the front plate are the same as those described above.
[0224] FIG. 1 shows a cross-sectional view of a display device according to one implementation. Specifically, FIG. 1 illustrates a display device in which a display section 400, a polymer film 100 having a first surface 101 and a second surface 102 on the display section 400, and a front panel 300 including a functional layer 200 are arranged, and an adhesive layer 500 is arranged between the display section 400 and the front panel 300.
[0225] The display unit 400 can display an image and can have a flexible characteristic.
[0226] The display unit 400 may be a display panel for displaying an image, such as a liquid crystal display panel or an organic electroluminescence display panel. The organic electroluminescence display panel may include a front polarizer and an organic EL panel.
[0227] The front polarizer may be disposed on a front surface of the organic electroluminescence panel. Specifically, the front polarizer may be attached to a surface of the organic electroluminescence panel on which an image is displayed.
[0228] The organic EL panel displays an image by self-emitting light in pixel units. The organic EL panel may include an organic EL substrate and a driving substrate. The organic EL substrate may include a plurality of organic electroluminescent units each corresponding to a pixel. Specifically, each may include a cathode, an electron transport layer, a light emitting layer, a hole transport layer, and an anode. The driving substrate may be drivingly coupled to the organic EL substrate. That is, the driving substrate may be coupled to the organic EL substrate so as to apply a driving signal such as a driving current to the organic EL substrate, thereby applying a current to each of the organic electroluminescent units to drive the organic EL substrate.
[0229] Also, an adhesive layer 500 may be included between the display unit 400 and the front panel 300. The adhesive layer may be an optically transparent adhesive layer, and is not particularly limited.
[0230] The front panel 300 is disposed on the display unit 400. The front panel may be located at the outermost periphery of a display device according to an embodiment and may protect the display unit.
[0231] The front panel 300 may include a polymer film and a functional layer. The functional layer may be at least one selected from the group consisting of a hard coating, a reflectance reducing layer, an anti-fouling layer, and an anti-glare layer. The functional layer may be coated on at least one surface of the polymer film.
[0232] [Method of manufacturing polymer film] In one implementation, a method for making a polymeric film is provided.
[0233] A method for producing a polymer film according to one embodiment includes the steps of preparing a polymer solution containing a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins in an organic solvent, transferring the polymer solution to a tank, extruding and casting the polymer solution in the tank, and then drying the polymer solution to produce a gel sheet, and heat-treating the gel sheet, where the heat treatment of the gel sheet is performed until the residual solvent is 1200 ppm or less.
[0234] Another embodiment of a method for producing a polymer film includes the steps of: polymerizing a diamine compound, a dianhydride compound, and a dicarbonyl compound in an organic solvent in a polymerization facility to prepare a polymer solution containing a polymer resin; transferring the polymer solution to a tank; extruding and casting the polymer solution in the tank, followed by drying to produce a gel sheet; and heat-treating the gel sheet, where the heat treatment of the gel sheet is performed at a temperature range of 80°C to 500°C for 5 minutes to 180 minutes.
[0235] Another embodiment of a method for producing a polymer film includes the steps of preparing a polymer solution containing a polymer resin in an organic solvent, moving the polymer solution to a tank, casting the polymer solution in the tank onto a belt and then drying it to produce a gel sheet, and heat-treating the gel sheet while moving it to produce a hardened film.
[0236] Referring to FIG. 2, a method for producing a polymer film according to one embodiment includes a step of simultaneously or sequentially mixing a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound in an organic solvent in a polymerization facility and reacting the mixture to prepare a polymer solution (S100), a step of transferring the polymer solution to a tank (S200), a step of purging with an inert gas (S300), a step of casting the polymer solution in the tank onto a belt and drying it to produce a gel sheet (S400), a step of heat-treating the gel sheet while moving it to produce a cured film (S500), a step of cooling the cured film while moving it (S600), and a step of winding up the cooled cured film by a winder (S700).
[0237] The polymer film is a film whose main component is a polymer resin selected from the group consisting of polyamide-based resins and polyimide-based resins.
[0238] In the method for producing the polymer film, a polymer solution for preparing the polymer resin is prepared by simultaneously or sequentially mixing a diamine compound and a dianhydride compound, or a diamine compound, a dianhydride compound and a dicarbonyl compound in an organic solvent in a polymerization facility, and reacting the mixture (S100).
[0239] In one implementation example, the polymer solution may be prepared by simultaneously introducing a diamine compound, a dianhydride compound, and a dicarbonyl compound into an organic solvent and reacting them.
[0240] In another embodiment, the step of preparing the polymer solution may include mixing and reacting the diamine compound and the dianhydride compound in a solvent to prepare a polyamic acid (PAA) solution, and dehydrating the polyamic acid (PAA) solution to prepare a polyimide (PI) solution.
[0241] In another embodiment, the step of preparing the polymer solution may include a step of first mixing and reacting the diamine compound and the dianhydride compound in a solvent to prepare a polyamic acid solution, and a step of second mixing and reacting the dicarbonyl compound with the polyamic acid solution to form amide bonds and imide bonds. The polyamic acid solution is a solution containing polyamic acid.
[0242] Alternatively, the step of preparing the polymer solution may include a step of primarily mixing and reacting the diamine compound and the dianhydride compound in a solvent to prepare a polyamic acid solution, a step of dehydrating the polyamic acid solution to prepare a polyimide solution, and a step of secondary mixing and reacting the dicarbonyl compound with the polyimide solution to additionally form amide bonds. The polyimide solution is a solution containing a polymer having imide repeat units.
[0243] In another embodiment, the step of preparing the polymer solution may include a step of first mixing and reacting the diamine compound and the dicarbonyl compound in a solvent to prepare a polyamide (PA) solution, and a step of second mixing and reacting the dianhydride compound with the polyamide (PA) solution to additionally form imide bonds. The polyamide solution is a solution containing a polymer having an amide repeat unit.
[0244] The polymer solution thus prepared may be a solution containing a polymer including one or more repeating units selected from the group consisting of polyamic acid (PAA) repeating units, polyamide (PA) repeating units, and polyimide (PI) repeating units.
[0245] For example, the polymer contained in the polymer solution may include imide repeat units resulting from the polymerization of the diamine compound and the dianhydride compound.
[0246] Alternatively, the polymer contained in the polymer solution may contain imide repeating units derived from the polymerization of the diamine compound and the dianhydride compound, and amide repeating units derived from the polymerization of the diamine compound and the dicarbonyl compound.
[0247] The solid content of the polymer solution may be 10% by weight to 30% by weight, or 15% by weight to 25% by weight, but is not limited thereto.
[0248] When the solid content of the polymer solution is within the above range, a polymer film can be efficiently produced in the extrusion and casting processes. In addition, the produced polymer film has excellent anti-blocking properties by securing a specific range of optical slip index, maximum static friction coefficient, and kinetic friction coefficient while maintaining a beautiful appearance and transparency. Furthermore, it has excellent mechanical properties that are hardly deteriorated even under high temperature and high humidity, and optical properties such as low yellowness, and has excellent folding properties with little deformation even when a certain level of load is sustained for a long time.
[0249] In one implementation, preparing the polymer solution may further include dosing a catalyst.
[0250] In this case, the catalyst may include at least one selected from the group consisting of β-picoline, acetic anhydride, isoquinoline (IQ), and pyridine-based compounds, but is not limited thereto.
[0251] The catalyst may be added in an amount of 0.01 to 0.4 molar equivalents based on 1 mole of the polyamic acid, but is not limited thereto.
[0252] Alternatively, the catalyst may be added in an amount of 0.01 wt % to 0.3 wt % based on the total weight of the polymer solution. Specifically, the catalyst may be added in an amount of 0.01 wt % to 0.2 wt %, 0.01 wt % to 0.15 wt %, 0.01 wt % to 0.1 wt %, or 0.02 wt % to 0.1 wt % based on the total weight of the polymer solution, but is not limited thereto.
[0253] The catalyst can increase the reaction rate and improve the chemical bonding strength between or within the repeating unit structures, and can also produce a film with low yellowness.
[0254] In one implementation, preparing the polymer solution may further include adding a dehydrating agent.
[0255] In this case, the dehydrating agent may be, but is not limited to, acetic anhydride.
[0256] The dehydrating agent may be added in an amount of 0.01 wt % to 10 wt %, 0.05 wt % to 5 wt %, or 0.05 wt % to 3 wt % based on the total weight of the polymer solution, but is not limited thereto.
[0257] The incorporation of the dehydrating agent has the effect of realizing a film with low yellowness and haze.
[0258] In other implementations, preparing the polymer solution may further include adjusting the viscosity of the polymer solution.
[0259] Specifically, the step of preparing the polymer solution may include: (a) preparing a first polymer solution by simultaneously or sequentially mixing and reacting a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound in an organic solvent; (b) measuring the viscosity of the first polymer solution to evaluate whether the target viscosity has been reached; and (c) if the viscosity of the first polymer solution does not reach the target viscosity, adding additional dianhydride compound or dicarbonyl compound to prepare a second polymer solution having the target viscosity.
[0260] The target viscosity may be 100,000 cps to 500,000 cps at room temperature. Specifically, the target viscosity may be 100,000 cps to 400,000 cps, 100,000 cps to 350,000 cps, 100,000 cps to 300,000 cps, 150,000 cps to 300,000 cps, or 150,000 cps to 250,000 cps at room temperature, but is not limited thereto.
[0261] The viscosity of the polymer solutions prepared in the step of preparing the first polymer solution is different from that of the step of preparing the second polymer solution, for example, the viscosity of the second polymer solution is higher than that of the first polymer solution.
[0262] The stirring speed when the first polymer solution is prepared is different from the stirring speed when the second polymer solution is prepared, for example, the stirring speed when the first polymer solution is prepared is faster than the stirring speed when the second polymer solution is prepared.
[0263] In another embodiment, the step of preparing the polymer solution may further include adjusting the pH of the polymer solution, which may be adjusted to 4 to 7, for example, 4.5 to 7, or 4.5 to less than 7, but is not limited thereto.
[0264] The pH of the polymer solution can be adjusted by adding a pH adjuster, which is not particularly limited but may include, for example, an amine-based compound such as an alkoxyamine, an alkylamine, or an alkanolamine, or a carboxylic acid-based compound such as acetic acid or butyric acid.
[0265] By adjusting the pH of the polymer solution within the above range, damage to equipment in subsequent processes can be prevented, defects in the film produced from the polymer solution can be prevented, the desired optical and mechanical properties in terms of yellowness index and modulus can be achieved, and the recovery and folding properties of the film can be improved.
[0266] The pH adjuster may be added in an amount of 0.01 wt % to 0.7 wt %, 0.01 wt % to 0.5 wt %, or 0.02 wt % to 0.4 wt % based on the total weight of the polymer solution, but is not limited thereto.
[0267] Alternatively, the pH adjuster may be added in an amount of 0.1 mol % to 10 mol % based on the total moles of monomers in the polymer solution.
[0268] Specifically, when a catalyst is added during preparation of a polymer solution, chemical imidization or thermal imidization is performed by the catalyst, and a transparent film with low yellowness can be produced by using an appropriate content. Meanwhile, such catalytic action may generate by-products or cause some physical properties to deteriorate, but the deterioration of physical properties can be improved by using a pH adjuster. For example, butyric acid can be used as a pH adjuster, and the butyric acid remains partially in the final film, and when the film is released from the force applied to it after being folded for a long time and then restored to a flat state, a transparent film with excellent folding properties can be realized.
[0269] In many cases, the chloride end group derived from the monomer for preparing the polymer resin and the Cl by-product generated from HCl generated during the film manufacturing process reduce reactivity, resulting in polymerization in a low molecular weight form. However, by using butyric acid as the pH adjuster, the reactivity of the catalyst can be effectively adjusted, reducing the amount of polymerization in a low molecular weight form and facilitating polymerization in a high molecular weight form.
[0270] Furthermore, there was a problem that the optical properties rapidly deteriorated when the low molecular weight polymers remaining in the polymer were dissolved after autoclave treatment (i.e., after treatment under harsh conditions of high temperature and high humidity).Also, conventional polymer films had the problem of forming a barrier layer in high temperature and high humidity environments, and additives such as clay with high moisture resistance were introduced to solve this problem, but in this case, problems occurred such as a deterioration in optical properties and poor compatibility.
[0271] On the other hand, by adding butyric acid during the polymerization process, as in the polymer film of the embodiment, the above problem can be solved, and a polymer film with excellent folding properties can be realized with almost no deterioration in optical and mechanical properties even after treatment under harsh conditions such as high temperature and high humidity.
[0272] In another embodiment, the step of preparing the polymer solution may further include a step of purging with an inert gas, which can remove moisture and reduce impurities, thereby increasing the reaction yield and achieving excellent surface appearance and mechanical properties of the final film.
[0273] The inert gas may be one or more selected from the group consisting of nitrogen, helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe), and radon (Rn), but is not limited thereto. Specifically, the inert gas may be nitrogen.
[0274] The molar ratio of the dianhydride compound to the dicarbonyl compound used to prepare the polymer solution may be 2:98 to 15:85. For example, the molar ratio may be, but is not limited to, 3:97 to 15:85, 5:95 to 15:85, 7:93 to 15:85, 2:98 to 25:75, 2:98 to 15:85, 20:80 to 100:0, 25:75 to 100:0, 30:70 to 100:0, 40:60 to 100:0, or 50:50 to 100:0.
[0275] The use of the dianhydride compound and the dicarbonyl compound in such a molar ratio is advantageous in that the mechanical and optical properties of the polymer film produced from the polymer solution can be achieved at target levels.
[0276] The diamine compound, the dianhydride compound, and the dicarbonyl compound are as described above.
[0277] In one embodiment, the organic solvent may be one or more selected from the group consisting of dimethylformamide (DMF), dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), m-cresol, tetrahydrofuran (THF), and chloroform. The organic solvent used in the polymer solution may be, but is not limited to, dimethylacetamide (DMAc).
[0278] Next, after the step of preparing the polymer solution, the polymer solution is transferred to a tank (S200).
[0279] Fig. 3 is a schematic diagram of a manufacturing process facility for the polymer film according to an embodiment. Referring to Fig. 3, the polymer solution is prepared in a polymerization facility 10, and the polymer solution thus prepared is transferred to and stored in a tank 20.
[0280] In this case, after the preparation of the polymer solution, a step of transferring the polymer solution to a tank is performed without a separate process. Specifically, the polymer solution prepared in the polymerization equipment is transferred to the tank and stored as is without a separate process of precipitation and redissolution for removing impurities. Conventionally, in order to remove impurities such as hydrochloric acid (HCl) generated during the preparation process of the polymer solution, the prepared polymer solution was purified in a separate process to remove the impurities, and the resulting solution was redissolved in a solvent. However, in this case, there was a problem that the loss of active ingredients was large during the process of removing the impurities, resulting in a decrease in yield.
[0281] Therefore, the preparation method according to one embodiment has the advantage of producing a film without a separate precipitation or re-dissolution process by fundamentally minimizing the content of impurities during the preparation process of the polymer solution, or by appropriately controlling certain impurities in subsequent processes even if they are present, so as not to deteriorate the physical properties of the final film.
[0282] The tank 20 is a place for storing the polymer solution before it is made into a film, and the temperature inside the tank 20 may be -20°C to 20°C.
[0283] Specifically, the internal temperature may be, but is not limited to, -20°C to 10°C, -20°C to 5°C, -20°C to 0°C, or 0°C to 10°C.
[0284] By controlling the internal temperature of the tank 20 within the above range, it is possible to prevent the polymer solution from deteriorating during storage, reduce the moisture content, and prevent defects in the film prepared therefrom.
[0285] The method for producing a polymer film may further include a step of vacuum degassing the polymer solution transferred to the tank 20 .
[0286] The vacuum degassing may be performed for 30 minutes to 3 hours after reducing the internal pressure of the tank to 0.1 bar to 0.7 bar. By performing vacuum degassing under such conditions, air bubbles in the polymer solution can be reduced, and as a result, surface defects in a film manufactured therefrom can be prevented and excellent optical properties such as haze can be achieved.
[0287] Also, the method for manufacturing a polymer film may further include purging the polymer solution transferred to the tank 20 with an inert gas (S300).
[0288] Specifically, the purging is performed by using an inert gas to purge the tank at an internal pressure of 1 to 2 atm. By performing nitrogen purging under such conditions, moisture in the polymer solution is removed and impurities are reduced, thereby increasing the reaction yield and achieving excellent optical properties such as haze and mechanical properties.
[0289] The inert gas may be one or more selected from the group consisting of nitrogen, helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe), and radon (Rn), but is not limited thereto. Specifically, the inert gas may be nitrogen.
[0290] The vacuum degassing step and the step of purging the tank with an inert gas are performed in separate steps.
[0291] For example, the vacuum degassing step may be performed, followed by a step of purging the tank with an inert gas, but is not limited thereto.
[0292] By performing the vacuum degassing step and / or the step of purging the tank with an inert gas, the physical properties of the surface of the prepared polymer film may be improved.
[0293] Thereafter, the method may further include storing the polymer solution in the tank 20 for 1 hour to 360 hours. At this time, the internal temperature of the tank may be maintained at -20°C to 20°C.
[0294] The method for producing the polymer film includes a step of extruding and casting the polymer solution in the tank 20, and then drying the same to produce a gel sheet (S400).
[0295] The polymer solution can be cast by a casting body such as a casting roll or a casting belt.
[0296] Referring to FIG. 3, in one implementation, the polymer solution can be coated onto a casting belt 30 as a casting body and dried while moving to produce a gel-like sheet.
[0297] When the polymer solution is injected onto the belt 30, the injection speed may be 300 g / min to 700 g / min. When the injection speed of the polymer solution satisfies the above range, the gel sheet can be formed uniformly with an appropriate thickness.
[0298] In addition, the casting thickness of the polymer solution may be 200 μm to 700 μm. By casting the polymer solution in this thickness range, it is possible to ensure appropriate thickness and thickness uniformity when the polymer solution is manufactured into a final film through drying and heat treatment.
[0299] As described above, the polymer solution has a viscosity of 100,000 cps to 500,000 cps at room temperature, and may be, for example, 100,000 cps to 400,000 cps, 100,000 cps to 350,000 cps, 150,000 cps to 350,000 cps, or 150,000 cps to 250,000 cps. By satisfying the above viscosity range, the polymer solution can be cast onto the belt with a uniform thickness without defects.
[0300] After casting the polymer solution, a gel sheet may be manufactured by drying for 5 to 60 minutes at a temperature of 60° C. to 150° C. Specifically, the drying may be performed for 10 to 50 minutes using hot air at 60° C. to 120° C. For example, the drying may be performed for 30 minutes using hot air at 100° C.
[0301] During the drying, the solvent of the polymer solution is partially or completely evaporated to produce the gel sheet.
[0302] The moving speed of the gel sheet on the casting body during the drying may be 0.1 m / min to 15 m / min, for example, 0.5 m / min to 10 m / min, but is not limited thereto.
[0303] The method for producing the polymer film includes a step of producing a cured film by heat-treating the gel sheet while moving the gel sheet (S500).
[0304] Referring to FIG. 3, heat treatment of the gel sheet may be performed by passing it through a heat curing device 40 .
[0305] The heat treatment of the gel sheet is performed for 5 minutes to 180 minutes in the range of 80°C to 500°C. Specifically, the heat treatment of the gel sheet may be performed for 5 minutes to 150 minutes while increasing the temperature at a rate of 2°C / min to 80°C / min in the range of 80°C to 500°C. More specifically, the heat treatment of the gel sheet may be performed by increasing the temperature at a rate of 2°C / min to 80°C / min in the temperature range of 80°C to 300°C.
[0306] According to another implementation, the gel sheet can be treated with hot air. When heat treatment is performed using hot air, the amount of heat can be uniformly applied. If the amount of heat is not uniformly distributed, satisfactory mechanical properties cannot be achieved. In particular, a satisfactory surface roughness cannot be achieved, and the surface tension may increase or decrease too much.
[0307] For example, the gel sheet may be treated with hot air for 5 to 60 minutes at a temperature range of 200° C. to 320° C. More specifically, the gel sheet may be treated with hot air at 250° C. to 290° C. for 25 to 35 minutes.
[0308] According to another embodiment, the heat treatment of the gel sheet may be performed in two or more stages.
[0309] According to other implementations, the heat treatment can be carried out until the residual solvent content in the film is 1200 ppm or less, or 1000 ppm or less.
[0310] The heat treatment is performed by carrying out the second heat treatment step after the first heat treatment step, and in this case, if the content of the organic solvent contained in the gel sheet exceeds 1000 ppm or 1200 ppm after carrying out the second heat treatment step, a third heat treatment step may be further carried out.
[0311] Specifically, the heat treatment may include a first heat treatment step performed at a temperature range of 60° C. to 120° C. for 5 minutes to 30 minutes, and a second heat treatment step performed at a temperature range of 150° C. to 350° C. for 30 minutes to 120 minutes.
[0312] For example, the third heat treatment step may be performed at a temperature in the range of 200° C. to 350° C. until the content of the organic solvent contained in the gel sheet is 1200 ppm or less, or 1000 ppm or less.
[0313] In addition, in the heat treatment step, the gel sheet may be stretched 1.01 to 1.05 times in the MD direction. Between the first heat treatment step and the second heat treatment step, the gel sheet may be stretched 1.01 to 1.05 times in the MD direction.
[0314] In the heat treatment step, the gel sheet may be stretched 1.01 to 1.05 times in the TD direction, and in the second heat treatment step, the gel sheet may be stretched 1.01 to 1.05 times in the MD direction.
[0315] The gel sheet may be stretched 1.01 to 1.05 times in the MD direction and the TD direction simultaneously, or may be stretched 1.01 to 1.05 times in the MD direction and then sequentially stretched 1.01 to 1.05 times in the TD direction.
[0316] By performing the heat treatment under such conditions, the gel sheet can be cured to have appropriate surface hardness and modulus, and the produced cured film can have excellent folding characteristics and optical properties, excellent optical and mechanical properties even under high temperature and high humidity conditions, and excellent restoring properties when the force applied to the film is released after maintaining a folded state for a long period of time.
[0317] The method for producing the polymer film includes a step of cooling the cured film while moving it (S600).
[0318] Referring to FIG. 3, the curing of the film is performed after passing through a thermal curing device 40, which may be performed using a separate cooling chamber (not shown), or may be performed by creating an appropriate temperature atmosphere without a separate cooling chamber.
[0319] The step of cooling the cured film while moving it may include a first temperature reduction step of reducing the temperature at a rate of 100°C / min to 1000°C / min, and a second temperature reduction step of reducing the temperature at a rate of 40°C / min to 400°C / min.
[0320] Specifically, the second temperature reducing step may be performed after the first temperature reducing step, and a temperature reducing rate of the first temperature reducing step may be faster than a temperature reducing rate of the second temperature reducing step.
[0321] For example, the maximum speed during the first temperature reduction stage is greater than the maximum speed during the second temperature reduction stage, or the minimum speed during the first temperature reduction stage is greater than the minimum speed during the second temperature reduction stage.
[0322] By performing the cooling step of the cured film in multiple stages as described above, the physical properties of the cured film can be further stabilized, and the optical and mechanical properties of the film established during the curing process can be more stably maintained for a long period of time. The moving speeds of the gel sheet and the cured film are the same.
[0323] The method for manufacturing the polymer film includes winding the cooled cured film by a winder (S700).
[0324] Referring to FIG. 3, winding of the cooled, cured film may utilize a roll-type winder 50 .
[0325] The ratio of the moving speed of the gel sheet on the belt during drying to the moving speed of the cured film during winding is 1:0.95 to 1:1.40. Specifically, the ratio of the moving speeds may be, but is not limited to, 1:0.99 to 1:1.20, 1:0.99 to 1:1.10, 1:1.0 to 1:1.05, or 1:1.01 to 1:1.05.
[0326] If the ratio of the moving speeds is outside this range, the mechanical properties of the cured film may be impaired, and flexibility and elasticity may decrease.
[0327] In the method for producing the polymer film, the thickness deviation (%) according to the following formula 1 may be 3% to 30%. Specifically, the thickness deviation (%) may be 5% to 20%, but is not limited thereto.
[0328] <General formula 1> Thickness deviation (%) = {(M1-M2) / M1} x 100 In the above general formula 1, M1 is the thickness (μm) of the gel sheet, and M2 is the thickness (μm) of the cooled, cured film when wound up.
[0329] The polymer film produced by the above-mentioned production method can exhibit excellent anti-blocking, optical, and mechanical properties. Such a polymer film can be applied to various applications requiring bending resistance, flexibility, durability, and transparency. For example, the polymer film can be applied to solar cells, semiconductor devices, sensors, etc. in addition to display devices.
[0330] The polymer film produced by the above-mentioned production method is as described above.
[0331] The above contents will be described in more detail with reference to the following examples, however, the following examples are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. (Examples and Evaluation Examples)
[0332] Example 1a A temperature-controllable double-jacketed 1L glass reactor was filled with dimethylacetamide (DMAc), an organic solvent, under a nitrogen atmosphere at 20°C, and then 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl (TFMB) (0.2 mol) was gradually added and dissolved. Then, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6-FDA) (0.1 mol) was gradually added and stirred for 1 hour. Then, terephthaloyl chloride (TPC) (0.1 mol) was added as a dicarbonyl compound and stirred for 1 hour to prepare a polymer solution.
[0333] Next, 17 g of acetic anhydride and 4.5 g of isoquinoline were added as a dehydrating agent and a catalyst to the polymer solution, and the mixture was stirred for 1 hour. Then, butanoic acid was added as a pH adjuster, and the mixture was stirred for 2 hours to prepare a polymer solution.
[0334] The obtained polymer solution was applied to a glass plate and then dried with hot air at 100°C for 30 minutes. The solution was then peeled off from the glass plate, fixed to a pin frame, and dried at 270°C for 30 minutes to obtain a polymer film with a thickness of 50 μm.
[0335] (Examples 2a, 3a, Comparative Examples 1a and 2a) As shown in Table 1 below, films were produced in the same manner as in Example 1, except that the types, contents, etc. of each reactant were changed.
[0336] The films produced in Examples 1a to 3a and Comparative Examples 1a and 2a were measured and evaluated for the following physical properties, and the results are shown in Table 1 below.
[0337] (Evaluation example 1a: Film thickness measurement) A digital micrometer 547-401 made by Mitutoyo Corporation, Japan was used to measure the thickness at five points in the width direction and the average value was used.
[0338] (Evaluation Example 2a: Measurement of residual solvent content in film) Using a thermogravimetric analyzer (DTG-50, manufactured by Shimadzu Corporation), the film was heated from room temperature to 300° C. at a heating rate of 15° C. / min under a nitrogen stream, and then held at 300° C. for 30 minutes. The total mass lost while the film was heated from 150° C. to 300° C. and while the film was held at 300° C. for 30 minutes was divided by the initial mass of the sample to determine the amount of residual solvent in the film.
[0339] (Evaluation Example 3a: Measurement of butyric acid content in film) TD-GC / MS analysis was used to measure the butyric acid content in the film. Specifically, 0.02g of the film sample was placed in a sample tube and then heated from 25°C to 300°C at a rate of 10°C / min. The gas generated by heating due to the temperature increase was adsorbed in an adsorption tube (Tenax), which was instantly heated (desorbed) and separated into each component by gas chromatography. The separated components were detected by a mass spectrometer, and the type and content of the components were analyzed from the obtained chromatogram.
[0340] The butyric acid content was measured in ppm based on the total weight of the film, and the results are shown in Table 1 below.
[0341] (Evaluation Example 4a: Transmittance and Haze Measurement) The light transmittance at 550 nm was measured using a haze meter NDH-5000W manufactured by Nippon Denshoku Industries Co., Ltd.
[0342] (Evaluation Example 5a: Yellowness Measurement) The yellow index (YI) was measured using a spectrophotometer (UltraScan PRO, Hunter Associates Laboratory) according to the CIE color system.
[0343] (Evaluation example 6a: In-plane phase difference measurement) The in-plane retardation (Ro) was measured using a retardation measuring instrument (Axoscan, manufactured by Axometrics, measuring wavelength 550 nm). The refractive index, which is the basic data of the retardation measuring instrument, was measured using an Abbe refractometer (NAR-4T, manufactured by Atago, measuring wavelength 589.3 nm).
[0344] (Evaluation Example 7a: Autoclave Treatment) A film measuring 2 cm in length, 10 cm in width, and 50 μm in thickness was placed in an autoclave and fixed, and the autoclave was filled with 2 L of water, and then closed and heated. At this time, the temperature of the autoclave was adjusted to 120° C., and the pressure was increased to 1.2 atm and treated for 24 hours. The autoclave was set to automatically turn off after the set time had elapsed. The outlet valve was opened, and the film was removed, and the physical properties were measured. The film was not immersed in water.
[0345] (Evaluation Example 8a: Bending resistance measurement) The film was repeatedly folded (one folding and unfolding counted as one folding) so that the radius of curvature of the 50 μm thick film was 3 mm. When deformation of the folded surface was not observed with the naked eye after 100,000 foldings, it was indicated with a circle, and when deformation of the folded surface was observed with the naked eye after 100,000 foldings, it was indicated with an x. The number of foldings was measured using a U-shape folding test device manufactured by Yuasa System Equipment Co., Ltd.
[0346] [Table 1]
[0347] As can be seen from Table 1, the polymer films of Examples 1a to 3a have a residual solvent content of 1200 ppm or less and a butyric acid content of 1200 ppm or less in the film, and therefore maintain excellent optical properties even after being treated under harsh conditions of high temperature and high humidity.
[0348] On the other hand, in the case of Comparative Examples 1a and 2a, in which no butyric acid was detected in the film and the residual solvent was present in an amount exceeding 1200 ppm, the low molecular weight polymer remaining in the polymer was eluted after autoclaving, and the optical properties such as haze, yellowness index, and in-plane retardation were significantly decreased.
[0349] Example 1b A temperature-controllable double-jacketed 1L glass reactor was filled with 585.68 g of an organic solvent, dimethylacetamide (DMAc), under a nitrogen atmosphere at 20°C, and then 0.2 mol of 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl (TFMB) was gradually added and dissolved. Then, 0.02 mol of 3,3',4,4'-benzophenone (BTDA) was gradually added and stirred for 1 hour. Then, 0.06 mol of isophthaloyl chloride (IPC) was added and stirred for 1 hour, and 0.12 mol of terephthaloyl chloride (TPC) was added and stirred for 1 hour to prepare a polymer solution. The obtained polymer solution was applied to a glass plate and then dried for 20 minutes with hot air at about 80°C to produce a gel sheet. The gel sheet was peeled off from the glass plate and fixed to a pin frame. When the gel sheet was fixed to the pin frame, it was stretched by about 1.03 times in a first direction and a second direction perpendicular to the first direction and then fixed. The fixed gel sheet was heat-treated at about 270° C. for 30 minutes, and a polymer film having a thickness of 50 μm was obtained.
[0350] With regard to the contents of TFMB, BTDA, TPC, and IPC, the number of moles of the dianhydride compound and the dicarbonyl compound based on 100 moles of the diamine compound are shown in Table 2.
[0351] (Examples 2b to 6b and Comparative Examples 1b to 3b) As shown in Table 2 below, films were produced in the same manner as in Example 1b, except that the type, content, and heat treatment time of each reactant were changed.
[0352] The films produced in Examples 1b to 6b and Comparative Examples 1b to 3b were measured and evaluated for the following physical properties, and the results are shown in Table 2 below.
[0353] (Evaluation example 1b: Film thickness measurement) A digital micrometer 547-401 made by Mitutoyo Corporation, Japan was used to measure the thickness at five points in the width direction and take the average value.
[0354] (Evaluation Example 2b: Measurement of residual solvent in film) After taking 0.02 g of the sample to be measured, a Purge & Trap-GC / MSD device was used to purge the sample at 30°C for 1 hour and collect the outgassed gas at 300°C for 10 minutes. Then, quantitative and qualitative analysis of the outgassed gas was performed to measure the amount of residual solvent.
[0355] (Evaluation Example 3b: Tensile strength and elongation at break measurement) Using an Instron universal testing machine UTM5566A, the sample was cut to 5 cm or more in the direction perpendicular to the main shrinkage direction and 10 mm in the main shrinkage direction, and attached to clips spaced 10 cm apart. The sample was then stretched at a rate of 12.5 mm / min at room temperature to obtain a stress-strain curve until breakage occurred. The tensile strength and elongation at break were measured from the stress-strain curve.
[0356] (Evaluation Example 4b: Modulus Measurement) Using an Instron universal testing machine UTM5566A, the sample was cut to 5 cm or more in the direction perpendicular to the main shrinkage direction and 10 mm in the main shrinkage direction, and attached to clips spaced 5 cm apart. The sample was stretched at a rate of 5 mm / min at room temperature to obtain a stress-strain curve until breakage occurred. The slope of the load against the initial deformation in the stress-strain curve was taken as the modulus (GPa).
[0357] (Evaluation Example 5b: Autoclave Treatment) A film measuring 2 cm in length, 10 cm in width, and 50 μm in thickness was placed in an autoclave and fixed, and the autoclave was filled with 2 L of water, and then closed and heated. At this time, the temperature of the autoclave was adjusted to 120° C., the pressure was increased to 1.2 atm, and the treatment was carried out for 24 hours or 72 hours. The autoclave was set to automatically turn off after the set time had elapsed. The outlet valve was opened, and the film was removed, and the physical properties were measured. The film was not immersed in water.
[0358] (Evaluation Example 6b: Transmittance Measurement) The light transmittance at 550 nm was measured using a haze meter NDH-5000W manufactured by Nippon Denshoku Industries Co., Ltd.
[0359] (Evaluation Example 7b: Yellowness Measurement) Yellowness index (YI) was measured using the CIE color system with a spectrophotometer (UltraScan PRO, Hunter Associates Laboratory).
[0360] (Evaluation Example 8b: Bending resistance measurement) The polymer film with a thickness of 50 μm was repeatedly folded (one folding and unfolding counts as one folding) so that the radius of curvature of the film was 3 mm. The case where the film did not break even after folding 100,000 times or more was indicated by O, and the case where the film broke before folding 100,000 times was indicated by X. The number of folding times was measured using a U-shape folding test device manufactured by Yuasa System Equipment Co., Ltd.
[0361] [Table 2]
[0362] As can be seen from Table 2, when the polymer films of Examples 1b to 6b were repeatedly folded to a curvature radius of 3 mm, the number of folding times until the film broke was confirmed to be 100,000 or more.
[0363] Furthermore, the polymer films of Examples 1b to 6b exhibited excellent results in terms of yellowness and transmittance, in addition to excellent folding properties.
[0364] Furthermore, the polymer films of Examples 1b to 6b also exhibited high values for mechanical properties such as tensile strength, elongation at break, and modulus, and still maintained excellent mechanical properties even after being subjected to harsh conditions of high temperature and high humidity for a certain period of time.
[0365] Example 1c A temperature-controllable double-jacketed 1L glass reactor was filled with the organic solvent dimethylacetamide (DMAc) under a nitrogen atmosphere at 20°C, and 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl (TFMB) was gradually added and dissolved. Then, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6-FDA) was gradually added and stirred for 1 hour. Then, terephthaloyl chloride (TPC) was added and stirred for 2 hours.
[0366] Next, pyridine as a catalyst and acetic anhydride as a dehydrating agent were added to the polymer solution, and butyric acid was added as a pH adjuster, and the mixture was stirred for 2 hours to prepare a polymer solution.
[0367] The obtained polymer solution was applied to a glass plate and then dried for 30 minutes with hot air at 80°C. The gel sheet was then dried by increasing the temperature at a rate of 2°C / min within the temperature range of 80°C to 300°C to obtain a polymer film with a thickness of 50 μm.
[0368] Table 3 shows the molar amounts of the diamine compound (TFMB), dianhydride compound (6FDA), and dicarbonyl compound (TPC) added.
[0369] In addition, in the case of the catalyst (pyridine) and butyric acid, the amounts added based on the total weight of the polymer solution are shown in Table 3 in terms of weight %.
[0370] (Examples 2c to 5c and Comparative Examples 1c to 3c) Films were produced in the same manner as in Example 1c, except that the types and contents of each reactant were different as shown in Table 3. In addition, in the cases of Comparative Examples 1c to 3c, the step of adding butyric acid was not carried out.
[0371] The films produced in Examples 1c to 5c and Comparative Examples 1c to 3c were measured and evaluated for the following physical properties, and the results are shown in Table 3 below.
[0372] (Evaluation Example 1c: Measurement of butyric acid content in film) TD-GC / MS analysis was used to measure the butyric acid content in the film. Specifically, 0.02g of the film sample was placed in a sample tube and attached, and then heated from 25°C to 300°C at a rate of 10°C / min. The gas generated by heating due to the temperature increase was adsorbed in an adsorption tube (Tenax), which was instantly heated (desorbed), and separated into each component by gas chromatography. The separated components were detected by a mass spectrometer, and the type and content of the components were analyzed from the obtained chromatogram.
[0373] The butyric acid content was measured in ppm based on the total weight of the film, and the results are shown in Table 3 below.
[0374] (Evaluation example 2c: Deformation angle evaluation (static bending test)) A polymer film measuring 150 mm in length, 20 mm in width and 50 μm in thickness was folded to a radius of curvature of 2 mm and left at 25° C. for 24 hours. After the force applied to the film was released, the internal angle of the film was measured.
[0375] (Evaluation example 3c: folding evaluation) The polymer film, 50 μm thick, was repeatedly folded (one folding and unfolding counts as one folding) until the radius of curvature became 2 mm. The folding speed was 60 rpm. The film was marked as pass if it was folded more than 200,000 times without breaking, and marked as fail if it broke before folding 200,000 times. The number of foldings was measured using a U-shape folding tester manufactured by Yuasa System Equipment Co., Ltd.
[0376] (Evaluation example 4c: Transmittance measurement) The light transmittance at 550 nm was measured using a haze meter NDH-5000W manufactured by Nippon Denshoku Industries Co., Ltd.
[0377] (Evaluation Example 5c: Yellowness Measurement) Yellowness index (YI) was measured using the CIE color system with a spectrophotometer (UltraScan PRO, Hunter Associates Laboratory).
[0378] (Evaluation Example 6c: Modulus Measurement) Using an Instron universal testing machine UTM5566A, the sample was cut to 5 cm or more in the direction perpendicular to the main shrinkage direction and 10 mm in the main shrinkage direction, and attached to clips spaced 5 cm apart. The sample was stretched at a rate of 5 mm / min at room temperature to obtain a stress-strain curve until breakage occurred. In the stress-strain curve, the slope of the load against the initial deformation was taken as the modulus (GPa).
[0379] [Table 3]
[0380] As can be seen from Table 3, the polymer films of Examples 1c to 5c exhibited excellent results in terms of recovery when returned to a flat state after being kept folded for a long period of time due to the presence of butyric acid remaining in the film. Specifically, the polymer films of Examples 1c to 5c exhibited deformation angles of 120° or more in the static bending test, whereas the polymer films of Comparative Examples 1c to 3c exhibited deformation angles of 115° or less, indicating poor static bending resistance.
[0381] In addition, in the case of the polymer films of Examples 1c to 5c, when the films were repeatedly folded to a curvature radius of 2 mm, the number of folding times until the films broke was more than 200,000 times, and it was confirmed that the films are easily applicable to foldable displays, flexible displays, rollable displays, etc. On the other hand, in the case of the polymer films of Comparative Examples 1c to 3c, the number of folding times did not exceed 200,000 times during the folding test, and the films broke.
[0382] Furthermore, the polymer films of Examples 1c to 5c still maintained excellent results in terms of mechanical properties such as modulus and optical properties such as transmittance and yellowness index, in addition to static bending properties and folding properties. [Explanation of symbols]
[0383] 10: Polymerization equipment 20: Tank 30: Belt 40:Thermosetting machine 50: Winder 100: Polymer film 101: 1st page 102:Second side 200: Functional layer 300: Front plate 400:Display section 500: Adhesive layer
Claims
1. The polymer resin is formed by polymerizing a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound, and includes butyric acid; The butyric acid is present in an amount of 1 ppm to 1000 ppm based on the total weight of the polymer film.
2. The polymer film for a display device according to claim 1 , wherein the butyric acid is represented by the following chemical formula T: <Chemical T>
3. 2. The polymer film for a display device according to claim 1, wherein the butyric acid is present in an amount of 1 ppm to 300 ppm based on the total weight of the polymer film.
4. 2. The polymer film for display devices according to claim 1, wherein when the film is left at 25° C. for 24 hours in a folded state so that the radius of curvature is 2 mm based on a thickness of 50 μm, and then the force applied to the film is released, the internal angle of the film is 120° or more.
5. 2. The polymer film for a display device according to claim 1, which can be folded 200,000 times or more before breaking when folded to a curvature radius of 2 mm based on a thickness of 50 μm.
6. 2. The polymer film for a display device according to claim 1, wherein the polymer resin comprises a repeating unit represented by the following formula A and a repeating unit represented by the following formula B in a molar ratio of 20:80 to 100:0: <Chemical A> <Case B> In the above chemical formulas A and B, E and J are each independently a substituted or unsubstituted divalent C 6 -C 30 Alicyclic group, substituted or unsubstituted divalent C 4 -C 30 Heteroalicyclic groups, substituted or unsubstituted divalent C 6 -C 30 Aromatic ring group, substituted or unsubstituted divalent C 4 -C 30 Aromatic heterocyclic group, substituted or unsubstituted C 1 -C 30 Alkylene group, substituted or unsubstituted C 2 -C 30 Alkenylene group, substituted or unsubstituted C 2 -C 30 Alkynylene group, —O—, —S—, —C(═O)—, —CH(OH)—, —S(═O) 2 , -Si(CH 3 ) 2 -, -C(CH 3 ) 2 , and -C(CF 3 ) 2 is selected from e and j are each independently selected from integers of 1 to 5; When e is 2 or more, two or more E's are the same or different, When j is 2 or more, two or more J's are the same or different, G is a substituted or unsubstituted tetravalent C 6 -C 30 Alicyclic group, substituted or unsubstituted tetravalent C 4 -C 30 Heteroalicyclic groups, substituted or unsubstituted tetravalent C 6 -C 30 Aromatic ring group, substituted or unsubstituted tetravalent C 4 -C 30 an aromatic heterocyclic group, wherein the alicyclic group, the heteroalicyclic group, the aromatic ring group, or the aromatic heterocyclic group is present alone or joined to each other to form a fused ring, or is a substituted or unsubstituted C 1 -C 30 Alkylene group, substituted or unsubstituted C 2 -C 30 Alkenylene group, substituted or unsubstituted C 2 -C 30 Alkynylene group, —O—, —S—, —C(═O)—, —CH(OH)—, —S(═O) 2 , -Si(CH 3 ) 2 -, -C(CH 3 ) 2 -, and -C(CF 3 ) 2 are linked by a linking group selected from the following:
7. The transmittance is 80% or more. The yellowness index is 5 or less.
2. The polymer film for a display device according to claim 1, having a modulus of 4.0 GPa or more.
8. Including a polymer film and a functional layer, The polymer film comprises a polymer resin formed by polymerizing a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound, and butyric acid.
9. A display unit; a front panel disposed on the display unit; the front panel includes a polymer film; The display device, wherein the polymer film comprises a polymer resin formed by polymerizing a diamine compound, a dianhydride compound, and optionally a dicarbonyl compound, and butyric acid.
Citation Information
Patent Citations
Polyimide-based aqueous dispersion and process for preparing same
JP1999049951A
Wiring board, manufacture thereof, and transfer original plate
JP2000236167A
Window film for display device, and display device including the same
JP2016125063A
Polyamide-imide resin and optical member containing polyamide-imide resin
JP2018119132A
Polyamide-imide copolymer and polyamide-imide film containing the same
JP2019510847A